Finite element analysis of RC deep beams with openings strengthened by carbon fiber reinforced polymer (CFRP) - Seow, Chun Mun (2015)
The research was to deal with overall behaviour of reinforced concrete deep beams with openings strengthened and un-strengthened by carbon fiber reinforced polymer at the shear span near support. The major objectives of the research are to determine the load-deflection curve, crack pattern and effects of opening shape for each beam with and without CFRP strengthening as well as identifying the most effective strengthening method. Due to limited research in numerical approach, this research was conducted by validating the finite element modelling results with experimental results. A total of eleven (11) beams with dimension of 120 x 600 x 2400 mm were modelled as simply supported beams in three-dimensional (31)) analysis by using finite element program, Ansys 12.0. In the research, two (2) types of opening shapes, rectangular (270 x 600mm) and circularised rectangular (270 x 330 mm, 0 270 mm) openings were placed at the mid shear span of the beams. In addition, reinforcement used was 2T16 for bottom bar, 2T10 for top bar, R6-300c/c for shear link and R6-150c/c for riser bar. Based on the analytical results, all the beams were failed in shear mode with cracking diagonally from the support to the sharp edge of the rectangular opening and around the circular edge of circularised rectangular opening. By comparing with solid beam, rectangular and circularised rectangular openings have resulted into a reduction in the beam bearing capacity by 70.6% and 68.2% respectively. As for CFRP strengthening beams with vertical surface wrap, horizontal surface wrap, vertical U-wrap and horizontal U-wrap, respectively, an increment of 10.4%, 13.6%, 28.0% and 36.0% for rectangular opening beams and 11.1%, 22.2%, 40.7% and 51.9% for circularised rectangular opening beams in terms of strength regain. Generally, there is good agreement on the crack patterns between FEA and experimental results.